1998
DOI: 10.1254/jjp.76.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tacrolimus Hydrate (FK506) Ointment on Spontaneous Dermatitis in NC/Nga Mice

Abstract: The effect of tacrolimus hydrate (FK506) ointment on spontaneous dermatitis in NC/Nga (NC) mice was examined. FK506 ointment (0.1-1%) suppressed the development of dermatitis and was also therapeutically effective against established dermatitis. Increases in CD4-positive T cells (helper T cells), mast cells, eosinophils and immunostaining of interleukin (IL)-4, IL-5 and IgE were confirmed in the skin of the NC mice, and FK506 ointment suppressed all of these changes. Increased plasma IgE was also confirmed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 20 publications
3
66
1
Order By: Relevance
“…The importance of these cytokines in atopic dermatitis was confirmed by the observation that corticosteroids and tacrolimus (FK-506) inhibit NF-kB activation. 22,23 In addition to the decrease in inflammatory cytokines, the improvement of dysregulated apoptosis in skin-homing cells may also contribute to the development and persistence of atopic dermatitis. 24 More recently, the importance of NFkB was proved by the observation that IkB␣ deficiency resulted in a sustained NF-kB response and severe widespread dermatitis in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of these cytokines in atopic dermatitis was confirmed by the observation that corticosteroids and tacrolimus (FK-506) inhibit NF-kB activation. 22,23 In addition to the decrease in inflammatory cytokines, the improvement of dysregulated apoptosis in skin-homing cells may also contribute to the development and persistence of atopic dermatitis. 24 More recently, the importance of NFkB was proved by the observation that IkB␣ deficiency resulted in a sustained NF-kB response and severe widespread dermatitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Topically active macrolide immunosuppressants, such as ascomycin and tacrolimus appear to provide comparable therapeutic potency. 22,23 Although the data from ongoing studies will be crucial in determining the safety of these agents in the long term, and also their place within the current therapeutic armamentarium available for patients with atopic dermatitis, these agents still have potential side-effects, such as systemic absorption. In contrast, NF-kB decoy ODN only exert local pharmacological effects for the following reasons: (1) ODN in serum were rapidly destroyed (within several hours), leading to a lack of systemic effects.…”
Section: Figure 7 Regression Of Atopic Dermatitis-like Skin By Nf-kb mentioning
confidence: 99%
“…Currently, on the other hand, topical applications of corticosteroids and tacrolimus (FK-506) are commonly used to treat AD, through immunosuppressive effects that are based on the inhibition of NF-kB activation. 31,32 In addition, Nakamura et al 33 reported that a single topical delivery of NF-kB decoy ODNs significantly regressed atopic dermatitis in NC/Nga mice. TARC is the primary chemokine in ADlike lesions of NC/Nga mice, 9 and TARC serum levels are closely related to disease activity in human AD.…”
Section: Antisense Oligonucleotides For Il-10 Alleviate Dermatitis T mentioning
confidence: 99%
“…8,9 It is reported that mast cells are increased in the dermis with dermatitis and that tacrolimus hydrate improves the spontaneous dermatitis in NC/Nga mice. 8 Furthermore, we have recently reported that ceramidastin efficiently reduces the mast cells in the mouse model.…”
mentioning
confidence: 99%
“…8,9 It is reported that mast cells are increased in the dermis with dermatitis and that tacrolimus hydrate improves the spontaneous dermatitis in NC/Nga mice. 8 Furthermore, we have recently reported that ceramidastin efficiently reduces the mast cells in the mouse model. 7 As shown in Figure 3, the application of the Pseudomonas ceramidase on the back of mice resulted in the significant increase in mast cells in the dermis.…”
mentioning
confidence: 99%